Ética corporativa no disclosure ambiental - Rossoni, Renata Luiza de Castilho (2024)
This thesis investigates the role of corporate ethics in environmental disclosure practices and their implications for organizational legitimacy. Within the context of the growing demand for transparency and socio-environmental responsibility, the research examines how companies use environmental disclosure to communicate their practices and impacts, exploring the discrepancies between what is disclosed and what is actually practiced. The novelty of this thesis is related to the analysis of the authenticity of ethical commitment in environmental disclosure practices for organizational legitimacy, offering means to examine the different configurations of corporate ethics in environmental disclosure and introducing the 'transformation strategy' as a path towards more genuine and sustainable business practices, integrating Kant's categorical imperative and Jonas' principle of co-responsibility. The thesis is composed of three interdependent articles, which offer a critical and comprehensive analysis of the interaction between ethics, disclosure and corporate legitimacy. The first article conducts a systematic review of the literature to map and analyze environmental disclosure practices in academia, analyzing 69 peer-reviewed articles. Through bibliographic coupling, the review identified six thematic clusters of discussion. The content analysis of these clusters allowed us to propose a conceptual framework that organizes the research field and a research agenda. The second article applies critical discourse analysis to examine Vale S.A.'s environmental disclosure practices after the Brumadinho disaster, with the aim of understanding how the company shaped its narratives to preserve its organizational legitimacy. Using integrated reports, legal documents, and media materials, the analysis reveals that Vale manipulated its discourse, adopting discursive strategies of idealization and abstraction. This article proposes a filtering model of environmental ethical commitment, which can be used to assess the authenticity of information disclosed by companies. The third article adopts Max Weber's ideal type method to develop a typology of environmental disclosure practices, based on the perceptions of environmental non-governmental organizations (NGOs). Based on in-depth interviews with representatives of eight NGOs, the study develops a typology of environmental disclosure practices, categorizing them into four types (illusionist, normative, transitional, and transformative), offering a new theoretical framework for the critical analysis of business practices. The research highlights the need for a transition from manipulative practices to a genuine commitment to sustainability, arguing that organizational legitimacy can only be achieved when disclosure practices are consistent with the truth. The theoretical contributions of the thesis are significant, especially with the introduction of the transformation strategy in legitimacy theory. This concept proposes that companies must go beyond traditional legitimation strategies, adopting continuous practices of sustainable innovation, ethics, and transparency to build lasting legitimacy. The social implications suggest that companies can strengthen their organizational legitimacy and contribute to a more just and sustainable society. The research also highlights the importance of stakeholders in promoting more transparent and responsible business practices, establishing new standards of excellence that can serve as a reference for the entire sector.